Developmental Associations Between Media Use and Adolescent Prosocial Behavior. (April 2022) - Fitzpatrick, Caroline; Boers, Elroy
Youth today spend a tremendous amount of time with digital media. The purpose of the present study was to estimate developmental associations between screen media use between the ages of 15 and 17 and corresponding changes in prosocial behavior. Participants ( N = 1, 509) were part of the Quebec Longitudinal Study of Child Development, a population-based study of children born in the province of Quebec, Canada. Youth self-reported internet and video game use and television or movies/DVD viewing, as well as prosocial behavior at the ages of 15 and 17. Analyses were conducted using multilevel linear modelling to account for between-, within-, and lagged-person effects. Internet and video game use accounted for less prosocial behavior at the within-person and lagged-person levels. Television use also accounted for lagged-person effects in prosocial behavior. Finally, internet use and television viewing contributed to between person differences in prosocial behavior. Our study presents strong statistical evidence that media use during adolescence can undermine the development of prosocial behavior.